Influence of mental effort on sound evaluations in virtual and real experimental environments - Himmelein, Hendrik; von Berg, Markus; Pörschmann, Christoph; Steffens, Jochen (Frontiers in Virtual Reality, 2025)
Psychoacoustic research increasingly relies on virtual reality (VR) to account for the complexity of acoustic scenarios and enhance the ecological validity of laboratory findings. However, recent studies suggest that virtual environments can alter mental effort compared to real-world settings, for example, through increased perceptual complexity which in turn may affect auditory perception.This could bias experimental outcomes and compromise the ecological validity of studies conducted in VR. To investigate this, a 2 × 2 between-subjects experiment was conducted to assess whether VR environments increase mental effort and thereby influence auditory perception. A real office environment was visually reconstructed in Unity and presented to the participants via a head-mounted display (HMD) and compared to its real counterpart. Participants in both environments were asked to retrospectively rate the loudness and unpleasantness of dynamically rendered binaural office noise scenarios presented via headphones and to report perceived sound sources. Moreover, participants were divided into two groups to induce different levels of mental effort. One group was asked to listen only to the sounds, while the other performed the Stroop Color-Word interference test in parallel. The results show no significant difference in the overall induced mental effort between environment conditions. Furthermore, performing the Stroop test had an effect on loudness and unpleasantness that was mediated by subjective effort. The results also suggest that auditory jugment depend primarily on individual sound properties, regardless of the visual environment.